Downsizing: costs, consequences, and best practices - Cascio, Wayne F. (Henry Stewart Talks, 2011)
Downsizing: Why it happens, Does it pay off?, Economic consequences, Layoffs around the world, Direct and indirect costs of layoffs, When downsizing is unavoidable, 10 avoidable mistakes in downsizing, HR practices that limit voluntary employee turnover, 10 tough questions about downsizing for managers, What survivors want to know, What to do when restructuring is necessary, Who goes? Who stays?, Corporate communications about restructuring, Restructuring: What to do